Tidal peritoneal dialysis versus ultrafiltration in type 1 cardiorenal syndrome: A prospective randomized study. Issue 12 (December 2019) - Al-Hwiesh, Abdullah K; Abdul-Rahman, Ibrahiem Saeed; Al-Audah, Nadia; Al-Hwiesh, Amani; Al-Harbi, Mousa; Taha, Abdulrahman; Al-Shahri, Abdulla; Ghazal, Sami; Amir, Rawan; Al-Audah, Nehad; Mansour, Hany; El-Mansouri, Mohammad; et al.
Background: Ultrafiltration is an alternative strategy to diuretic therapy for the treatment of patients with acute decompensated heart failure. Little is known about the efficacy and safety of peritoneal dialysis in patients with acute decompensated heart failure complicated by acute cardiorenal syndrome. Methods: We randomly assigned a total of 88 patients with type 1 acute cardiorenal syndrome to a strategy of ultrafiltration therapy (44 patients) or tidal peritoneal dialysis (44 patients). The primary endpoint was the change from baseline in the serum creatinine level and left ventricular function represented as ejection fraction, as assessed 72 and 120 h after random assignment. Patients were followed for 90 days after discharge from the hospital. Results: Ultrafiltration therapy was inferior to tidal peritoneal dialysis therapy with respect to the primary endpoint of the change in the serum creatinine levels at 72 and 120 h ( p = 0.041) and ejection fraction at 72 and 120 h after enrollment ( p = 0.044 and p = 0.032), owing to both an increase in the creatinine level in the ultrafiltration therapy group and a decrease in its level in the tidal peritoneal dialysis group. At 120 h, the mean change in the creatinine level was 1.4 ± 0.5 mg/dL in the ultrafiltration therapy group, as compared with 2.4 ± 1.3 mg/dL in the tidal peritoneal dialysis group ( p = 0.023). At 72 and 120 h, there was a significant difference in weight loss between patients in the ultrafiltration therapy group and those in the tidal peritoneal dialysis group ( p = 0.025). Net fluid loss was also greater in tidal peritoneal dialysis patients ( p = 0.018). Adverse events were more observed in the ultrafiltration therapy group ( p = 0.007). At 90 days post-discharge, tidal peritoneal dialysis patients had fewer rehospitalization for heart failure (14.3% vs 32.5%, p = 0.022). Conclusion: Tidal peritoneal dialysis is a safe and effective means for removing toxins and large quantities of excess fluid from patients with intractable heart failure. In patients with cardiorenal syndrome type 1, the use of tidal peritoneal dialysis was superior to ultrafiltration therapy for the preservation of renal function, improvement of cardiac function, and net fluid loss. Ultrafiltration therapy was associated with a higher rate of adverse events.